PENGARUH OWNERSHIP RETENTION, LEVERAGE, TIPE AUDITOR, JENIS INDUSTRI TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL - kumala, kadek sintya; Sari, Maria M. Ratna (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Intellectual capital is an asset wealth of human resources in which the asset has a role in the operation of a company which will have an impact on increasing the value of the company that awakened the motivation for creating a competitive advantage. The purpose of this study was to obtain empirical evidence related to the effect of ownership retention, leverage, auditor type, industry type on intellectual capital disclosure. The data used in this research is secondary data from the company's annual report to IPO IDX sampled in 2009-2013. Sampling methods with particular consideration used to obtain samples with specific criteria so get as many as 80 companies. Technical linear analysis performed in this study using SPSS 16. This study shows results that retetention ownership, leverage, auditor type has a significant positive effect on the intellectual capital disclosure. And the last variable is the industry type do not affect the intellectual capital disclosure.
Keywords: Intellectual Capital Disclosure, Ownership Retention, Leverage, Auditor Type, Industry Type